2021
DOI: 10.1186/s13293-020-00346-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of sex differences in dietary copper-fructose interaction-induced alterations of gut microbial activity in relation to hepatic steatosis

Abstract: Background Inadequate copper intake and increased fructose consumption represent two important nutritional problems in the USA. Dietary copper-fructose interactions alter gut microbial activity and contribute to the development of nonalcoholic fatty liver disease (NAFLD). The aim of this study is to determine whether dietary copper-fructose interactions alter gut microbial activity in a sex-differential manner and whether sex differences in gut microbial activity are associated with sex differe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…Interestingly, the bacterial phenotypes annotated from the liver in our study were distinct from those reported in previous studies on the gut (Supplemental Figure S12). We identified 34 phyla, 102 classes, 248 orders, 429 families, 865 genera, and 1367 species with a relative abundance greater than 0.01. The most abundant taxa at each level are listed in Figure E–J.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the bacterial phenotypes annotated from the liver in our study were distinct from those reported in previous studies on the gut (Supplemental Figure S12). We identified 34 phyla, 102 classes, 248 orders, 429 families, 865 genera, and 1367 species with a relative abundance greater than 0.01. The most abundant taxa at each level are listed in Figure E–J.…”
Section: Resultsmentioning
confidence: 99%
“…Sex hormones and sex chromosomes are the two major factors driving sex-based characterization of the differences in the microbiome between the male and female sexes ( 30 ). A previous study revealed that sex-specific microbiomes may play an essential role in the incidence of NAFLD and obesity ( 31 ).…”
Section: Link Of Microbiota To the Non-alcoholic Fatty Liver Disease ...mentioning
confidence: 99%
“…Male and female sexes have different microbiome species associated with fat distribution, and sometimes, the same family and genus of microbiomes have different associations with fat distribution in the two sexes ( 32 ). Postmenopausal females with estrogen deficiency display a higher risk for NAFLD progression to fibrosis owing to the alteration of gut microflora ( 30 ). Male patients with NAFLD showed a decreasing trend in microbial α-diversity, an increasing trend in the abundance of genera Dialister , Streptococcus , and Bifidobacterium species, and a decreasing trend in the abundance of the genera Phascolarctobacterium , Mogibacteriaceae , Rikenellaceae , and Peptococcaceae .…”
Section: Link Of Microbiota To the Non-alcoholic Fatty Liver Disease ...mentioning
confidence: 99%
“…However, other subgroups couldn’t be performed become of the absence of detailed data. Second, sex hormones and chromosomes have a definite impact on the differences in microbiomes between men and women ( 49 ). A previous study revealed that a sex-specific microbiome might play a critical role in NAFLD and obesity incidence ( 50 ).…”
Section: Limitationsmentioning
confidence: 99%